Cerebral oxygenation following decompressive hemicraniectomy for the treatment of refractory intracranial hypertension - Stiefel, Michael F; Heuer, Gregory G; Smith, Michelle J; Bloom, Stephanie; Maloney-Wilensky, Eileen; Gracias, Vincente H; Grady, M Sean; LeRoux, Peter D (Journal of neurosurgery, 2004)
Medically intractable intracranial hypertension is a major cause of morbidity and mortality after severe brain injury. One potential treatment for intracranial hypertension is decompressive hemicraniectomy (DCH). Whether and when to use DCH, however, remain unclear. The authors therefore studied the effects of DCH on cerebral O2 to develop a better understanding of the effects of this treatment on the recovery from injury and disease. The study focused on seven patients (mean age 30.6 +/- 9.7 years) admitted to the hospital after traumatic brain injury (five patients) or subarachnoid hemorrhage (two patients) as part of a prospective observational database at a Level I trauma center. At admission the Glasgow Coma Scale (GCS) score was 6 or less in all patients. Patients received continuous monitoring of intracranial pressure (ICP), cerebral perfusion pressure (CPP), blood pressure, and arterial O2 saturation. Cerebral oxygenation was measured using the commercially available Licox Brain Tissue Oxygen Monitoring System manufactured by Integra NeuroSciences. A DCH was performed when the patient's ICP remained elevated despite maximal medical management. All patients tolerated DCH without complications. Before the operation, the mean ICP was elevated in all patients (26 +/- 4 mm Hg), despite maximal medical management. After surgery, there was an immediate and sustained decrease in ICP (19 +/- 11 mm Hg) and an increase in CPP (81 +/- 17 mm Hg). Following DCH, cerebral oxygenation improved from a mean of 21.2 +/- 13.8 mm Hg to 45.5 +/- 25.4 mm Hg, a 114.8% increase. The change in brain tissue O2 and the change in ICP after DCH demonstrated only a modest relationship (r2 = 0.3). These results indicate that the use of DCH in the treatment of severe brain injury is associated with a significant improvement in brain O2.